Analysis of Charge and Current Flow in the LCR Series Circuit via Chebyshev Wavelets (Contemporary Mathematics, 2024)
In this research paper, an investigation of charge and current flow in an LCR series circuit has been presented. For this purpose, basis functions of Chebyshev wavelets of the second kind have been utilized. The proposed method involves representing the highest-order derivatives as a series of basis functions using Chebyshev wavelets. In order to demonstrate the effectiveness of this approach, numerical examples have been provided, and their results are presented to show the accuracy of the proposed scheme.
Keywords: Chebyshev wavelets; LCR circuit; function approximation; numerical examples